Egg-yolk- and a liposome-based extenders: refrigeration time and effects on ram semen quality - de Almeida, Rogério Araújo [UNESP]; da Silva, Luan Sitó [UNESP]; de Lima, Luiz Gustavo Ferreira [UNESP]; Lourencetti, Flávio Augusto [UNESP]; Freitas-Dell´Aqua, Camila [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Oba, Eunice [UNESP] (FapUNIFESP (SciELO), 2025)
Sperm cells require time to adjust to lower temperatures. While some studies have established stabilization periods ranging from two to four hours for ovine semen, the exploration of longer periods of stabilization remains limited. The objective of the study is to evaluate the 12-hour refrigeration curve during ovine semen cryopreservation and the impact of a diluent medium containing egg yolk and liposomes. Eight mixed-breed rams (½ Dorper and ½ Santa Inês) provided two ejaculates each, divided into two groups. Group A used a commercial egg yolk-based diluent (Botu-Bov® - Botupharma Ltda, Brazil), while Group B used a commercial liposome-based diluent (OptiXcell®, IMV Technologies, France). Semen was packaged in French straws, cooled, cryopreserved, and thawed for analysis. Group A exhibited superior values (P < 0.05) in progressive motility (MP), progressive linear velocity (VSL), straightness (STR), and linearity (LIN) post-thawing and after 3 hours at 37°C (TTR). Conversely, Group B showed higher (P < 0.05) values for path velocity (VAP), curvilinear velocity (VCL), lateral head displacement amplitude (ALH) post-thawing, and VAP, VSL, VCL, and ALH after TTR. Flow cytometry revealed Group A's higher (P > 0.05) plasma and acrosomal membrane integrity and membrane stability. However, Group B exhibited greater (P > 0.05) superoxide anion generation and lipid peroxidation, indicative of higher oxidative stress. In conclusion, the egg yolk-based diluent outperformed the diluent containing liposomes in sperm kinetic parameters evaluated by CASA, although liposomes showed increased oxidative stress, 12 hours of refrigeration at 5.0°C is an alternative viable for semen cryopreservation in sheep.